P159 Preliminary experience of a tailored ild pulmonary rehabilitation program and inspiratory muscle training delivered in a hospice and home setting. (15th November 2017) - AlQuaimi, M; McNeillie, L; Donaldson, C; Harper, J; Hartley, J; Cassidy, S; Bourke, AM; Simpson, J; Ward, C; Forrest, I
Abstract : Background: Dysponea, muscle wasting, and fatigue are common manifestations in interstitial lung disease (ILD). Pulmonary rehabilitation programmes (PRP) aim to improve symptoms and quality of life in ILD but research is very limited about the role and feasibility of inspiratory muscle training (IMT) in PRP. Methods: Six patients with a mixed disciplinary team diagnosis of ILD (5 males, median age 80 range 67–85) participated in a tailored PRP either in an IMT (n=3) or control group (n=3). PRP involved three days of exercises, one conducted in a hospice day therapy unit and two at home. The PRP session involved aerobic, strength, and stretching exercises with integrated education and relaxation sessions. Both groups received the same PRP, supplemented in the IMT group by the use of a POWERbreathe Medic plus respiratory muscle trainer. The trainer use consisted of 30 breaths twice daily with personalised resistance levels of 40% Maximal Inspiratory Pressure (MIP), which was measured and adjusted weekly. ILD outcome measures were recorded before and after PRP. Results: All patients completed the PRP with adherence of ≥80% for the full program. There were no major complications or adverse events and patients reported liking and enjoying the PRP and environmental setting. Table 1 report the PRP outcomes. Description: there was a considerable prevalence of baseline limitation in term of depression, anxiety, fatigue severity scale (FSS), forced vital capacity (FVC) and six-minute walk test (6MWT). These limitations were maintained after PRP and there was a reduction in FVC in both groups, consistent with disease progression. In the IMT group there was a trend for an improvement in MIP, 6MWT, FSS, and visual analogue fatigue scale and a maintenance of quadriceps strength when compared with the control group. Conclusion: We believe this is the first description of a successful pilot of bespoke ILD PRP in a hospice and home setting. The PRP was acceptable and appreciated by both patients and healthcare professionals. IMT during PRP for ILD in a hospice setting is feasible and longitudinal measurements of fatigue, 6MWT, and MIP were practicable end points that warrant further study.